Rozważania na tle art. 9 Kodeksu karnego wykonawczego - Mrozek, Kamila; Sitnik, Katarzyna (Wydawnictwo Uniwersytetu Wrocławskiego, 2013)
This article is dedicated to issues connected with immediate execution of a court sentence, which is presently governed by the provisions of Art. 9 of the Executive Criminal Code. The above principle has been confronted with adjournment of an imprisonment order, which constitutes an exception to the principle of immediate execution. The paper also presents statistical data concerning individuals convicted by a final sentence but for some reasons not yet placed in a penal institution. This phenomenon significantly limits the functioning of the said principle, which assumes an immediate execution procedure after a court sentence becomes final.
Keywords: kara pozbawienia wolności; odroczenie odbywania kary; przeludnienie zakładów karnych; wykonalność kary